Effects of indolebutyric acid, stem cutting positions and substrates on the vegetative propagation of Stevia rebaudiana Bertoni - Pigatto, Guilherme Bortoloso; Gomes, Erik Nunes; Tomasi, Jéssica de Cássia; Ferriani, Aurea Portes; Deschamps, Cícero (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
Stevia rebaudiana Bertoni is a species with high economic importance because of the production of natural sweeteners with a low caloric value. The seed production of this species is irregular and micropropagation techniques raise the cost of seedling production. Thus, this study aimed to optimize the vegetative propagation of a Brazilian accession of this species through stem cuttings. The plant material was collected from one-year-old mature plants. Two experiments were carried out to determine the best indolebutyric acid (IBA) concentration to improve rooting and to evaluate the interaction between the stem cutting position (apical, medium and basal) and substrates (Tropstrato HT®, vermiculite, and vermiculite/Tropstrato HT® mixture). The rooting of the stem cuttings was affected by the IBA concentrations. The application of 710 mg L-1 was recommended for higher rooting percentages. The stem cuttings from the apical branch region had higher rooting percentages than the medium and basal areas (means of 70, 45.8 and 7.5%, respectively). Similar results were observed for the root numbers, root lengths and root fresh and dry mass. The substrate Tropstrato HT® promoted higher rooting percentages and lower mortality than vermiculite.